Analisis Tingkat Keandalan Jaringan Distribusi 13,8 KV Dengan Menggunakan Metode Ria - Yaser, Fahroli; Zakri, Azriyenni Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study proposes calculating and assess the level of reliability of the distribution system. This study calculates reliability index based on the value of failure occurred. The method used in this study is Reliability Index Assessment (RIA), where is this method takes into account interruption momentary. This study takes a case study on one of the largest private companies in Pekanbaru, make up to the mark of six feeders. Based on extinguishing data obtained that reliability index becomes smaller and can be differentiated between permanent fault and temporary fault. The calculation results show in the reliability index of SAIFI, SAIDI, and MAIFI based on the type of fault. The results of this calculation will compare with SPLN and IEEE standards. Comparison of all the results of SAIFI average value is 0.2199 times/year/customer compared to SPLN standard of 3.2 times/year/customer and IEEE standard of 1.45 times/year/customer has a high level of reliability. The value of SAIDI average value is 8.0437 hours/year/costumer compared to SPLN standard of 21 hours/year/customer and IEEE standard of 2.3 hours/year/customer has a unreliable level of reliability, caused of this condition transformer in feeder 3 gets maintenance. The value of MAIFI average value is 1.3 times/year/customer compared to IEEE standard of 5 times/year/customer has a high level of reliability.Keywords: MAIFI, SAIDI, SAIFI, RIA, reliability